The Use of Discourse Markers by Iraqi Secondary Schools Pupils (Journal Of Educational and Psychological Researches, 2018)
This research aims at investigating pupils’ ability in using discourse markers which are identified in the English textbooks of secondary schools. Four texts are chosen from third intermediate class. The four texts are short stories of different topics.                                                          This research hypothesizes that there are no statistical significant differences among Iraqi intermediate pupils’ ability in using textual and interpersonal discourse markers.      After surveying ,collecting  and analyzing data statistically, the research revealed that the higher frequent use of  discourse markers is textual markers is better , i.e. pronouns .